2006
DOI: 10.1002/chp.74
|View full text |Cite
|
Sign up to set email alerts
|

Professional isolation and performance assessment in New Zealand

Abstract: The identification of physicians at risk for professional isolation may enable the prevention of poor performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This is not an unusual finding in the international literature. A Canadian study found 610 deficiencies in 305 physicians who underwent assessment because of performance concerns . The same study reported that 69% of issues concerned knowledge, 14% for medical records, technical skills 10%, clinical judgment 5%, and communication skills 2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not an unusual finding in the international literature. A Canadian study found 610 deficiencies in 305 physicians who underwent assessment because of performance concerns . The same study reported that 69% of issues concerned knowledge, 14% for medical records, technical skills 10%, clinical judgment 5%, and communication skills 2%.…”
Section: Discussionmentioning
confidence: 99%
“…A small proportion of these will have deficits severe enough to warrant attention from a regulatory authority. These doctors present different educational challenges than their more capable colleagues, as often these doctors have poor insight regarding their standard of practice, are professionally marginalized, and have cognitive impairment or concurrent illness . Usually, personalized remedial education programs are developed for these doctors .…”
Section: Introductionmentioning
confidence: 99%
“…Those occupational therapists who are probably the most autonomous of all, private practitioners, have identified that there are barriers to maintaining professional competence inherent in their role including professional isolation, time and finances (Courtney & Farnworth, 2003). Professional isolation has been identified as a risk factor for poor performance in other health fields, most notably medicine (St George, 2006). As workplace support, mentoring and motivation of therapists are significant influences on competency maintenance (Lysaght, Altschuld, Grant & Henderson, 2001), it is not surprising that isolated practitioners face challenges in competency maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Solo medical practice has also been compared with group practice using variables such as clinical skills, prescribing patterns, continuing education, patient satisfaction and quality of care. In some studies, solo practice resulted in clinical measures that were comparable with group practice11 but there has been an overriding concern that solo practice may have an adverse effect upon clinical performance 12 13 14 15…”
mentioning
confidence: 99%